Effect of the Width-Diameter Ratio of Twisted Tape Inserts in Heat Exchanger Tubes on Heat Transfer - Farah Abd-Alsalam Ibrahim; Nabil Jamil Yasin; Tahseen Ali Jabbar (ASEAN Journal for Science and Engineering in Materials, 2026)
This study investigated how the width–diameter ratio of twisted tape inserts and tube size influence heat transfer and pressure loss in circular heat exchanger tubes under turbulent air flow. A three-dimensional steady CFD model with an SST k–omega turbulence closure simulated uniformly heated tubes containing constant pitch tapes across multiple diameters and ratios. Grid independence and literature validation established numerical reliability. A mid-size tube consistently delivered the best thermal performance, and the largest tested width–diameter ratio produced the highest Nusselt enhancement while keeping pressure penalties manageable. The inserts markedly outperformed a plain tube in overall heat transfer. Performance improves because swirl from the tape strengthens core to wall mixing and thins the thermal boundary layer without excessively raising friction at suitable geometries. Findings guide compact, energy-efficient exchanger design by identifying geometry combinations that maximize heat transfer for practical pumping power. Designers can apply the framework across diverse operating conditions.